L’agriculture vivrière à Madingou (République du Congo) : moyen de subsistance et d’acquisition des revenus - André Wilfrid Landa; Duck Duvais Miyalou (Études Caribéennes)
In Madingou, as in other small towns of the Republic of Congo, to solve the problem of food and income acquisition, the population is often oriented towards the practice of food agriculture. This study aims to analyze the role of subsistence agriculture in the survival of the population of Madingou. It was based on documentary research, field observations, interviews with resource persons and the administration of the questionnaire among 106 households selected in the Moukokotadi and Mboukoudou neighbourhoods, and concerned only the heads of producer households or their spouses. This study has shown that food farming in Madingou is a predominantly female activity and is of interest to households of any socio-professional status. It is practiced using rudimentary culture systems and techniques; its production is for self-consumption and then for sale. The income from the sale allows the population to meet its various needs.